2018
DOI: 10.1016/j.rmed.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Anti-parietal cell autoimmunity is associated with an accelerated decline of lung function in IPF patients

Abstract: Anti-parietal cell autoimmunity is detected in some IPF patients and is associated with an accelerated decline of lung function. Anti-parietal cell autoimmunity may promote lung fibrosis progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Proton pump inhibitors target the H+/K+ ATPase, which has recently been shown to be expressed in the hyperplastic alveolar epithelium in patients with IPF [13]. Use of anti-acid medication has been associated with a decreased rate of decline in FVC and improved survival in some observational studies in patients with IPF [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Proton pump inhibitors target the H+/K+ ATPase, which has recently been shown to be expressed in the hyperplastic alveolar epithelium in patients with IPF [13]. Use of anti-acid medication has been associated with a decreased rate of decline in FVC and improved survival in some observational studies in patients with IPF [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Since we had to choose one defined condition for our experiments we expected to miss some of the possible targets. Indeed, we did not identify autoantigens that have previously been shown to be associated with disease severity or survival in IPF, such as anti-vimentin, anti heat-shock protein 70 or anti-parietal cell antibodies (Beltramo et al, 2018;Kahloon et al, 2013;Li et al, 2017;Taillé et al, 2011).…”
Section: Discussionmentioning
confidence: 70%
“…In our study, MZB1 levels correlated positively with tissue IgG and negatively with lung function parameters, suggesting a common association of IPF progression with antibody mediated autoimmunity (Schiller et al, 2017). Indeed, it has been shown that high levels of autoantibodies against vimentin (Li et al, 2017), heat-shock protein 70 (Kahloon et al, 2013), periplakin as well as anti-parietal cell antibodies (Beltramo et al, 2018; Taillé et al, 2011), were associated with a more severe disease in IPF.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] The responsible antigen(s) remain(s) to be identified, but several studies point to the alveolar epithelial cell as a possible target of autoimmunity in IPF, as circulating autoantibodies directed toward epithelial cells have been detected by different groups [34][35][36][37][38][39][40][41] including our group. 42,43 Immune senescence due to pathologic aging may contribute to this abnormal immune status. 44 Interestingly, some genetic forms of pulmonary fibrosis are associated with autoimmunity and autoimmune disorders.…”
Section: Introductionmentioning
confidence: 99%